PENDAMPINGAN PERIZINAN DAN PENYUSUNAN LAPORAN KEUANGAN PADA SWALAYAN SURYA - Zubaidah, Siti (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2021)
The purpose of this service is to form/develop a group of people as entrepreneurs who are economically independent with the specific target to be achieved is to provide assistance in licensing and preparing financial reports at Surya supermarket (Muhammadiyah Charity) Kwadungan Village, Ngasem District, Kediri Regency. The partner in this service is Surya supermarket (Muhammadiyah Charity) Kwadungan Village, Ngasem District, Kediri Regency. The problem with partners is that they have not been able to carry out licensing according to the OSS method and have not been able to prepare financial reports correctly. The method used in solving partner problems is to provide assistance and tutorials in licensing and preparing financial reports at the Muhammadiyah Charity Enterprises of Kediri Regency. The output of this service is a financial management module and software for preparing financial reports.